Aplikasi Augmented Reality (AR) untuk Pengenalan Varietas Anggur Hasil Balitbangtan - Dhila Aprilianti; Annisa Amanda Nelvi; Amata Fami (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2023)
Augmented reality is a combination of two worlds: virtual and real world, which mean objects in the virtual world can be displayed in the real world. The use of augmented reality in the introduction media, in the form of applications on android smartphones designed as the introduction of varieties of grape from Balitbangtan. Balitbangtan (Badan Penelitian dan Pengembangan Pertanian) is the highest structural office in the Ministry of Agriculture with the task of researching, developing and innovating in agriculture. The purpose of this application is to introduce the grape varieties from Balitbangtan in the ebook, “Budidaya Tanaman Anggur” in a more interactive and easy to understand way by displaying objects in 3D virtual and can make sounds containing explanations about the variety of grape from Balitbangtan. This application will show three types of grape varieties of Balitbangtan with markers according to the image of the grape variety in the ebook. Apps are built using Unity, Vuforia, and Blender. The method used in this study is the method of collection of data questionnaires (wags) which is a data collection technique performed by asking questions or written statements to respondents to answer them. The questionnaire was conducted by researchers by spreading a list of questions to students and millennial farmers who read the e-book. Results from questionnaires found that 80% of respondents agreed with the implementation of augmented reality in the introduction of Balitbangtan grape varieties with category “Totally Agree”.Method that used in this research is MDLC method (multimedia development life cycle). There are six steps in this method such as concepting, designing material collection, creating, testing, and distribution. We are testing applications and user satisfaction. Testing user satisfaction done through survey or questionnaire. survey done by researcher with spread question list to college student and millennial farmer that read ebook Budidaya Tanaman Anggur and they have installed and using application introduction to grape variety from Balitbangtan. The result of the survey found that 80% respondent agree with augmented reality applied to the introduction to grape variety from Balitbangtan.